Optimization of the extraction of phenolic compounds from olive pomace using response surface methodology - Wendt Böhmer-Maas, Bruna; Murowaniecki Otero, Deborah; Zambiazi, Rui Carlos; Camargo Aranha, Bianca (Revista Ceres, 2025)
Extraction of olive oil gives rise to large quantities of pomace and liquid effluents, since on average only 21% of the weight of the olive corresponds to oil, the remaining 79% consists of water, bark, pulp and stone. With the intention to make available new forms of use of this residue, this research was proposed, with aimed to optimize the extraction of phenolic compounds from olive pomace resulting from oil extraction using methanolic extracts. The analysis of phenolic compounds (TPC) and the evaluation of the antioxidant activity (AA) were performed by spectrophotometry, and the individual phenols were carried out by LC-ESI-qTOF-MS. The data were evaluated by the application of the response surface methodology (RSM). The condition that promoted the highest TPC in an extract was using 40% methanol, 70°C and 180 minutes (extract 7). The highest AA was in the extract obtained with 40% methanol, 45 °C and 180 minutes (extract 5). The highest individual phenol sum (IPS) was in the extract with 80% methanol, 45 ºC and 180 minutes (extract 6). Therefore, it is possible to conclude that the RSM was an interesting tool to measure the best conditions for extraction of phenolic compounds from olive pomace.